Feasibility study of functional facilities (ice factory) and level of need for ice supporting capture fisheries activities at the Meureudu Fish Landing Base - Imelda Agustina; Ratna Mutia Aprilla; Taufiqurrahman Taufiqurrahman; Rizwan Thaib; Makwiyah Chaliluddin; Salmarika Salmarika; Alvi Rahmah (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2024)
Pidie Jaya Regency is one of the districts that contributes to capture fisheries production in Aceh Province. Pidie Jaya Harbor is the Fish Landing Base (PPI) in Meureudu. As capture fisheries activities developed at PPI Meureudu, the local government began to pay attention to building several port facilities such as basic facilities, functional facilities and supporting facilities. Supporting facilities or supporting facilities are facilities that support fishing activities at the port, one of these facilities is an ice factory. The ice factory at PPI Meureudu belongs to the Aceh marine and fisheries service which was built in 2012. The Aceh Development Fund (ADF) built an ice factory with a production capacity of up to 30 tons/day at the Meureudu Fish Landing Base (PPI), through an environmentally friendly technology program for industry fishing process. Under normal conditions, the PPI Meureudu ice factory is currently producing ice cubes in excess of fishermen's needs, so ice cubes are sold by fishermen operating in the Peulimbang and Peudada areas, Bireuen Regency. Sometimes, when the fish catch is abundant, ice is not enough to meet the ice needs for ships at PPI Meureudu and must be supplied from Sigli, Pidie Regency. This study aims to determine the need for ice in fishing and handling operations to the feasibility of the ice factory business at PPI Meureudu. This research was carried out for one month, namely in November 2022 at the Meureudu Fish Landing Base (PPI), Meureudu City, Kec. Meureudu, Pidie Jaya Regency. The data used in this study are primary data secondary data. using business feasibility analysis. The results showed that the need for ice blocks at PPI Meureudu for fishing operations within one month was 221.80 tons, and the need for ice for fish handling activities at PPI Meureudu within one month required the amount of ice to be 2,879 blocks of ice or 144,864 tons which is the result of the analysis financial value obtained from the NPV Rp. 95,761,105 can be said to be feasible because the value is greater than 0. At an IRR value of 5% it can be said to be feasible because the results of the IRR calculation are greater than the discount factor, and a Net B/C value of 1 is said to be a breakeven project because = 1. These three values have been carried out in the Meureudu PPI block ice factory business that business it is worth continuing.Keywords:Business FeasibilityIce Block FacilityPidie Jaya